Long Non-Coding RNAs in the Cell Fate Determination of Neoplastic Thymic Epithelial Cells - Iaiza, Alessia; Tito, Claudia; Ganci, Federica; Sacconi, Andrea; Gallo, Enzo; Masciarelli, Silvia; Fontemaggi, Giulia; Fatica, Alessandro; Melis, Enrico; Petrozza, Vincenzo; Venuta, Federico; Marino, Mirella; et al. (Frontiers in Immunology, 2022)
Thymic Epithelial Tumors (TETs) arise from epithelial cells of the thymus and are very rare neoplasms comprising Thymoma, Thymic carcinoma, and Thymic Neuroendocrine tumors that still require in-depth molecular characterization. Long non-coding RNAs (lncRNAs) are emerging as relevant gene expression modulators involved in the deregulation of several networks in almost all types of human cancer, including TETs. LncRNAs act at different control levels in the regulation of gene expression, from transcription to translation, and modulate several pathways relevant to cell fate determination under normal and pathological conditions. The activity of lncRNAs is strongly dependent on their expression, localization, and post-transcriptional modifications. Starting from our recently published studies, this review focuses on the involvement of lncRNAs in the acquisition of malignant traits by neoplastic thymic epithelial cells, and describes the possible use of these molecules as targets for the design of novel therapeutic approaches specific for TET. Furthermore, the involvement of lncRNAs in myasthenia gravis (MG)-related thymoma, which is still under investigation, is discussed.